2016
DOI: 10.1016/j.jcin.2016.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Impact of Atrial Fibrillation in Patients With Severe Aortic Stenosis Undergoing Transcatheter Aortic Valve Replacement

Abstract: In the large dataset of the SOURCE XT registry, the presence of either pre-existing or NOAF increased all-cause and cardiac mortality and bleeding events. NOAF was associated with increased stroke rates at long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
95
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(104 citation statements)
references
References 30 publications
4
95
1
4
Order By: Relevance
“…Post‐hoc data from the PARTNER trial and other observational and meta‐analytical studies have shown new‐onset AF to be associated with greater risk for cerebrovascular events at 30 days. However, despite the anticipated adverse effects of AF, we did not observe statistically significant differences in 30‐day risk of outcomes compared with patients in sinus rhythm in this study.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Post‐hoc data from the PARTNER trial and other observational and meta‐analytical studies have shown new‐onset AF to be associated with greater risk for cerebrovascular events at 30 days. However, despite the anticipated adverse effects of AF, we did not observe statistically significant differences in 30‐day risk of outcomes compared with patients in sinus rhythm in this study.…”
Section: Discussioncontrasting
confidence: 80%
“…Compared with paroxysmal AF, persistent AF has been linked with higher risk [4,5]. Recent evidence also suggests that new-onset AF, which has an incidence of 1-38% in TAVR studies, has a pronounced effect on stroke and mortality after TAVR [2,[6][7][8][9]. While procedural factors such as TAVR access can modify the risk of new-onset AF, valve type and post-dilation have also been considered to influence risk of neurological events in these patients [2,3,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This association was maintained even after adjusting for other known independent risk factors. 11 In fact, discontinuing beta blockers was found to be the strongest predictor for periprocedural AF in those with known AF as well as for NOAF. There are several potential explanations including a rebound phenomenon, in which the abrupt withdrawal of beta blockers leads to a reactive increase in plasma catecholamines, increased numbers of beta adrenergic receptors (β-AR) and/or an alteration in their affinity for adrenergic agonists, or rebound hypersensitivity to sympathetic stimulation.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we showed that discontinuing beta blockers prior to TAVR was associated with increased risk of AF. This association was maintained even after adjusting for other known independent risk factors . In fact, discontinuing beta blockers was found to be the strongest predictor for periprocedural AF in those with known AF as well as for NOAF.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,[8][9][10] The American Society of Echocardiography (ASE) and the European Association for Cardiovascular Imaging (EACVI) have proposed a classification for LVEF into normal (>51% in male and >53% in female), mildly abnormal (>40%-51% in male and to 53% in female), moderately abnormal (≥30%-≤40%), and severely abnormal (<30%) thus including different thresholds for males and females. 11 This distinction might be of clinical significance, given the predominance of female patients in most TAVI registries 2,12 and also considering the usually better outcome of female patients. 13 However, the clinical value of this classification for expanded risk stratification based on baseline LVEF has not been studied in patients undergoing TAVI.…”
Section: Introductionmentioning
confidence: 99%